Measurement of quantum coherence in thin films of molecular quantum bits without post-processing12. Issue 50 (3rd June 2019) - Lenz, Samuel; Kern, Bastian; Schneider, Martin; van Slageren, Joris
Abstract : A novel Fabry–Pérot pulsed EPR resonator with very good microwave magnetic field homogeneity allows facile measurement of thin films of molecular quantum bits. Abstract : Thin film deposition of molecular quantum bits may further their integration into devices. Current electron paramagnetic resonance equipment is ill-suited for thin film investigations of spin dynamics. We present a 35 GHz Fabry–Pérot resonator enabling such measurements and demonstrate its use in the study of different molecular quantum bits.